Behrooz File System (BFS) - Shafiee Sarjaz, Behrooz (University of Waterloo, 2015)
In this thesis, the Behrooz File System (BFS) is presented, which provides an in-memory distributed file system. BFS is a simple design which combines the best of in-memory and remote file systems. BFS stores data in the main memory of commodity servers and provides a shared unified file system view over them. BFS utilizes backend storage to provide persistency and availability. Unlike most existing distributed in-memory storage systems, BFS supports a general purpose POSIX-like file interface. BFS is built by grouping multiple servers’ memory together; therefore, if applications and BFS servers are co-located, BFS is a highly efficient design because this architecture minimizes inter-node communication. This pattern is common in distributed computing environments and data analytics applications. A set of microbenchmarks and SPEC SFS 2014 benchmark are used to evaluate different aspects of BFS, such as throughput, reliability, and scalability. The evaluation results indicate the simple design of BFS is successful in delivering the expected performance, while certain workloads reveal limitations of BFS in handling a large number of files. Addressing these limitations, as well as other potential improvements, are considered as future work.
Keywords: File system; Distributed; In-memory; POSIX; ZooKeeper; FUSE; Computer Science